Phytoplankton of the middle and lower stretches of the Uruguay River - O'farrell, Ines (2014)
The Uruguay River is one of the largest lowland rivers of South America. At its middle section, its course is altered by the Salto Grande Reservoir, which constitutes a discontinuity factor affecting the main limnological characteristics and the plankton communities. In this chapter we present a review of the available information on the phytoplankton of the middle and lower stretches since 1978, a short time before the start of the Salto Grande dam operation. The studies show that phytoplankton communities are regulated by two main forces: water discharge and seasonality, with higher phytoplankton abundances usually associated to the warm season, and lower ones to high water discharge. Human activities in the river basin have been inducing changes in the potamoplankton. From the 70’s to the 90’s the studies reported that potamoplankton was dominated by diatoms, with chlorophyceans co-dominating in summer. During the last decade, the phytoplankton assemblage showed a higher proportion of cryptophytes, which together with diatoms and chlorophyceans, conform the typical potamoplankton of the river. Recently, blooms of Cyanobacteria appeared in the river during the summer, mainly near the littoral zone, favoured by a combination of high temperatures and enhanced water column stability.